Fungsi Kearifan Lokal Dalam Menjaga Kelestarian Lingkungan Hidup Di Desa Penglipuran - I Gede Januariawan (Jurnal Penelitian Agama Hindu, 2021)
This article examines the function of local wisdom of the Penglipuran Village community in preserving the environment in the insistence of modern life. Data obtained by in-depth interview techniques, observation, and by conducting a literature study. The discussion uses the functional structural theory from Talcot Parsons which states there are four important functions needed by all systems, namely adaptation, goal attainment, integration, latency. The analysis shows that the Penglipuran community can still survive to maintain local wisdom in terms of environmental conservation because traditional villages as a system function properly good. Hulu Apad Adat Elders and Adat leaders (Bendesa Adat), as implementers and enforcers of customary law both awig-awig and perarem who regulate environmental issues related to Hindu religious teachings, Tri Hita Karana, which regulates harmonious relations with God, fellow human beings, and natural environment. The effort made by the Penglipuran community to maintain local wisdom and at the same time be able to adapt to modern life is by maintaining the pattern of values ​​inherited from their ancestors. In the field of pawongan, the community maintains local wisdom to maintain harmony in neighboring and community life, among others; maintaining the existence of a hatchery or a road that gives access to neighboring yards, maintaining the existence of blended corals to avoid polygamous marriages which are believed to cause disharmony in family life, and to strengthen community social relations in addition to cooperation in carrying out mutual social activities and also cooperation in carrying out religious ceremonial activities, there is also local wisdom of nyangkepang sager. Sangkep or meeting with the tradition of eating together with a menu of rice with a side dish of salted fish (sager) added with grated coconut. In addition to fostering familiarity with fellow community members, it also means teaching a simple lifestyle that is different from the consumptive lifestyle of modern times. The preservation of traditional values ​​is passed on by parents to the next generation from an early age. Likewise, in the field of palemahan, environmental cleanliness, forest preservation is still maintained by protecting it through the enforcement of customary law whose sanctions are linked to beliefs or religions, namely Hinduism. Actions that cause damage to the environment are believed to be sinful acts. Adat community obedience to comply with these Customary rules when analyzed with the theory of validity and legal enforceability of Meuwissen. that the principles of Customary Law meet the requirements; social or factual enforceability, juridical enforceability and moral enforceability.